Case report: Cryptogenic giant brain abscess caused by Providencia rettgeri mimicking stroke and tumor in a patient with impaired immunity - Zhao, Yu; Lian, Baorong; Liu, Xudong; Wang, Qizheng; Zhang, Daxue; Sheng, Qi; Cao, Liming (Frontiers in Neurology, 2022)
The highly lethal cryptogenic brain abscess can be easily misdiagnosed. However, cryptogenic brain abscess caused by Providencia rettgeri is rarely reported. We present the case of a cryptogenic Providencia rettgeri brain abscess and analyze the clinical manifestations, imaging findings, treatment, and outcome to improve the level of awareness, aid in accurate diagnosis, and highlight effective clinical management. A 39-year-old man was admitted to the hospital after experiencing acute speech and consciousness disorder for 1 day. The patient had a medical history of nephrotic syndrome and membranous nephropathy requiring immunosuppressant therapy. Magnetic resonance imaging revealed giant, space-occupying lesions involving the brain stem, basal ganglia, and temporal-parietal lobes without typical ring enhancement, mimicking a tumor. Initial antibiotic treatment was ineffective. Afterward, pathogen detection in cerebrospinal fluid using metagenomic next-generation sequencing revealed Providencia rettgeri. Intravenous maximum-dose ampicillin was administered for 5 weeks, and the patient's symptoms resolved. Cryptogenic Providencia rettgeri brain abscess typically occurs in patients with impaired immunity. Our patient exhibited a sudden onset with non-typical neuroimaging findings, requiring differentiation of the lesion from stroke and brain tumor. Metagenomic next-generation sequencing was important in identifying the pathogen. Rapid diagnosis and appropriate use of antibiotics were key to obtaining a favorable outcome.